Open Ocean Particle Flux Variability From Surface to Seafloor. Issue 9 (10th May 2021) - Cael, B. B.; Bisson, Kelsey; Conte, Maureen; Duret, Manon T.; Follett, Christopher L.; Henson, Stephanie A.; Honda, Makio C.; Iversen, Morten H.; Karl, David M.; Lampitt, Richard S.; Mouw, Colleen B.; Muller‐Karger, Frank; et al.
Abstract: The sinking of carbon fixed via net primary production (NPP) into the ocean interior is an important part of marine biogeochemical cycles. NPP measurements follow a log‐normal probability distribution, meaning NPP variations can be simply described by two parameters despite NPP's complexity. By analyzing a global database of open ocean particle fluxes, we show that this log‐normal probability distribution propagates into the variations of near‐seafloor fluxes of particulate organic carbon (POC), calcium carbonate, and opal. Deep‐sea particle fluxes at subtropical and temperate time‐series sites follow the same log‐normal probability distribution, strongly suggesting the log‐normal description is robust and applies on multiple scales. This log‐normality implies that 29% of the highest measurements are responsible for 71% of the total near‐seafloor POC flux. We discuss possible causes for the dampening of variability from NPP to deep‐sea POC flux, and present an updated relationship predicting POC flux from mineral flux and depth. Plain Language Summary: Understanding the oceanic cycles of carbon and other elements important for life, as well as how ocean life influences the Earth's climate, we must understand how the carbon fixed by phytoplankton during photosynthesis is consumed and redistributed throughout the ocean. How much carbon is fixed at a given place and time varies substantially based on a number of factors; out of this complexity, however, emerges a simple description in terms of a probability distribution: The log‐normal. Here, we show that this log‐normal description propagates all the way from the upper ocean to the seafloor. We find that this log‐normal description is robust, applying both to the global open ocean and to individual locations. Our results help resolve the long‐standing question of to what extent seafloor communities rely on a steady supply of energy versus large pulses. Our results also shed light on the known connection between the vertical transport of organic carbon and those of calcium carbonate and opal. We also find that variability in primary production is dampened on its way to the seafloor in a consistent fashion. Key Points: The log‐normal probability distribution is a robust description of variability in net primary production and particulate organic carbon (POC) flux in both the upper open ocean and the deep sea We present an updated flux relationship for organic carbon, calcium carbonate, and opal ∼70% of the POC deposition to the deep seafloor occurs during high‐flux periods which cover only ∼30% of the time